Zakat Distribution Management and Poverty Issues: A Study in the State of Kedah - Abdul Hamid, Solahuddin; Dahaman @ Dahlan, Mohd Akram; Rofie, Mohamad Khadafi (Supporting Academic Initiatives Foundation, 2023)
The poor are known as asnafand this group of people is often prioritized in the distribution of zakat. However, poverty remains a major issue in the country's socioeconomic development and continues to shackle the community. The study sought to identify the various issues of poverty among the poor asnaf, as well as determine the mechanism used by the Kedah State Zakat Board (LZNK) to address these issues.Data were gathered through interviews with LZNK management representatives and the distribution of questionnaires to 400 asnaf who had received zakat assistance. The survey found that the majority of respondents were pleased with the value and duration of the assistance they received. However, the zakat received cannot lift them out of poverty. In theory, zakat distribution meets the asnaf’s daily needs, but in practice, they continue to be reliant on welfare.Hence, effective strategies are needed to address the poverty issues faced by the society